A COMPREHENSIVE SURVEY ON THE PROFICIENCY OF UNDERHAND SERVING SKILLS AMONG EIGHTH-GRADE FEMALE STUDENTS IN THE VOLLEYBALL EXTRACURRICULAR PROGRAM AT SMP NEGERI 6 LAWE SIGALA-GALA - Muhammad Donni; Ladipin; Afrizal (RADJA PUBLIKA, 2025)
This descriptive quantitative survey study aims to determine the proficiency level of underhand serving skills among eighth-grade female students participating in the volleyball extracurricular program at SMP Negeri 6 Lawe Sigala-Gala during the 2025/2026 academic year. The research employed a standardized testing methodology, utilizing the AAHPER (American Alliance for Health, Physical Education and Recreation) Serving Accuracy Test as the primary instrument for data collection. The subject pool consisted of 20 female students, each granted five attempts to execute an underhand serve into a target grid scoring system (1-4 points per serve, with a maximum possible score of 20). The collected data were analyzed using descriptive statistics, including measures of central tendency and frequency distribution, and categorized into five proficiency levels: Very High, High, Moderate, Low, and Very Low. The findings reveal a notably high level of underhand serve proficiency among the participants. The mean score achieved was 69.75 out of a maximum 100, with a highest individual score of 90 and a lowest of 50. The distribution across categories showed that 70% of students (n=14) were classified in the 'High' proficiency category, 20% (n=4) in the 'Very High' category, and the remaining 10% (n=2) in the 'Moderate' category. No students fell into the 'Low' or 'Very Low' categories. Furthermore, 90% of the participants (n=18) met or exceeded the minimum passing standard. These results strongly indicate that the majority of the students have successfully mastered the fundamental technique of the underhand serve. The study concludes by recommending the continuation of regular and structured practice, the sustained application of engaging, game-based pedagogical approaches, and the ongoing institutional support through the provision of adequate facilities and infrastructure to maintain and further elevate skill levels.